2023
DOI: 10.3390/su15021606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of COVID-19 Pandemic on Food Choice Motives: A Systematic Review

Abstract: The economic crisis caused by the COVID-19 pandemic has effected the global economy, with the main changes expected to affect human life in the future, including food consumption. However, could this pandemic be assumed as a threshold for the suspension of the usual rules behind food choices? This review highlights the changes in food choice motivations before, during, and after the pandemic that have been reported in the literature to date to answer the research question on the changes in food choice motives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 114 publications
0
19
0
Order By: Relevance
“…The processes of social transformation underway in recent decades have radically changed the world of food and the agri-food sector [ 1 , 2 , 3 ]. The COVID-19 crisis has changed people’s daily routines: isolation, remote working, increased sedentary lifestyle and the frequency of meals and snacks, mood changes, anxiety and health concerns have conditioned the choices and reasons for food preferences, the choice of outlets and purchasing methods [ 4 , 5 , 6 , 7 , 8 ]. In the current post-COVID-19 period, the European consumer is looking for quality and healthy foods with natural ingredients to protect themselves from disease, protect the environment and provide sustainability to local economies [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The processes of social transformation underway in recent decades have radically changed the world of food and the agri-food sector [ 1 , 2 , 3 ]. The COVID-19 crisis has changed people’s daily routines: isolation, remote working, increased sedentary lifestyle and the frequency of meals and snacks, mood changes, anxiety and health concerns have conditioned the choices and reasons for food preferences, the choice of outlets and purchasing methods [ 4 , 5 , 6 , 7 , 8 ]. In the current post-COVID-19 period, the European consumer is looking for quality and healthy foods with natural ingredients to protect themselves from disease, protect the environment and provide sustainability to local economies [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that food motives and related eating habits have changed during this time and especially during the COVID-19 pandemic [ 43 ]. A few studies, however, suggest that the changes in food motives have been temporary and long-term effects cannot be determined yet [ 44 , 45 ]. In a Finnish study, most people reported that the pandemic did not change their eating habits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has not had a significant impact on nutritional quality and sensory appeal, which are two of the main factors influencing food choices [27]. Over the years, experts have prioritized the promotion of medical guidelines regarding nutrient intake and proper consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have also provided recommendations for a balanced diet that does not prohibit the consumption of specific food products. According to the analyzed data, it appears to be more feasible to promote the exploration of healthier food choices among consumers, such as fresh fruits, vegetables, and whole foods [27]. Positive predictors and significant determinants of healthy eating attitudes are motives that indicate healthier perceptions, such as weight control, maintaining a healthy diet, and choosing organic food [28].…”
Section: Literature Reviewmentioning
confidence: 99%